Recent Education Trends and Their Hypothesized Impact on Rural Districts - E. Robert Stephens (Journal of Research in Rural Education, 1994)
A number ofdevelopments in education that originated during the past 5 years or became more pronounced during this time are ofgreat significance for the nation's rural school systems. I agree that most ofthese developments have the potential for enhancing the institutional capacity of rural districts to respond to the growing pressures on public education.